Treated microporous membranes
By treating the surface of the microporous membrane, a membrane with anti-clogging properties and good oil retention rate is formed, which solves the problem in the existing technology that microporous membranes are prone to congestion under high pressure, achieving efficient oil-water separation and extending service life.
Patent Information
- Application Number
- CN202380045721.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-14
- Filing Date
- 2023-05-17
- Publication Date
- 2025-01-21
AI Technical Summary
The existing microporous membranes are easily congested by residual oil and other contaminants when operating under high pressure, resulting in a decrease in flow rate and a decrease in filtration efficiency, and it is difficult to extend its service life.
Through the surface of the microfil membrane, the membrane is formed by sircitane treatment, and enhances the plug -in properties and oil retention rate of the membrane through the synthesis response, polysaccharide treatment and the formation of polysaccharide gel layer.
It achieves maintaining high flow rates and good oil retention under high pressure, while extending the service life of the microporous membrane and reducing the occurrence of scaling.
Smart Images

Figure BDA0005176274100000051 
Figure BDA0005176274100000221 
Figure BDA0005176274100000231
Abstract
Description
Technical Field
[0001] The present invention relates to a method for treating the surface of a microporous membrane and a treated microporous membrane. The present invention also relates to a method for treating a filter device and a treated filter device. Background Art
[0002] In the United States, oil and gas wells pump billions of gallons of co-produced water each year. The natural "oil" in the well is actually a multiphase emulsion of oil, water, and natural gas. Generally speaking, all three fluids are present in every hydrocarbon well and well effluent. For example, bilge water contains high hydrocarbon concentrations and has a wide range of carbon numbers. Bilge water is typically a mixture of scrubbing chemicals, rust, sewage, boiler water chemicals, lubricating and hydraulic oils, foaming fluids, gray water, metals, soot, bacteria, dust, etc.
[0003] The oil needs to be separated from these effluents due to its value and environmental concerns. This is usually done by gravity settling in large tanks, which requires capital and a lot of space that is not always available on site. Gases can be easily separated in mechanical separators or by reducing the pressure within the storage vessel. In the case of heavy oils and many emulsified fluid systems, the raw fluid is heated to change the density of the oil and water by heating the lighter fractions and essentially agitating their molecular structure, making these fluids easier to separate. Water is then a byproduct.
[0004] Filled microporous membranes are known to be low-cost, highly effective and environmentally friendly separation media for separating oil from byproduct waters, such as bilge water and other effluents mentioned above. However, like most filter media, over a period of time, the filter membranes may become clogged with residual oil and other contaminants. Such clogs reduce the flow rate and, thereby, the efficiency of the filter device. It is desirable to provide a microporous membrane for use as an extended life filter media, which is capable of operating at high pressures, has improved anti-clog properties and good oil retention, while maintaining high flow rates. Summary of the invention
[0005] A method is provided for treating the surface of a microporous membrane comprising an organic thermoplastic substrate; a finely divided, substantially water-insoluble inorganic filler distributed throughout the substrate; and a network of interconnected pores communicating throughout the microporous membrane. The method comprises, in sequence: (1) contacting at least one surface of the membrane with a treatment composition to form a silane-treated membrane, the treatment composition comprising: (a) an acrylic polymer prepared from a mixture of vinyl monomers, the mixture comprising: (i) (meth) acrylic monomers and (ii) silane-functional acrylic monomers; and (b) a base, wherein the acrylic polymer is contacted with the filler present in the substrate; (2) subjecting the silane-treated membrane formed in (1) to conditions sufficient to achieve a condensation reaction between the filler and the acrylic polymer; (3) contacting at least one surface of the silane-treated membrane with a dispersion comprising an amine-functional polysaccharide dispersed in an aqueous medium containing an organic acid to form a polysaccharide-treated membrane; (4) contacting at least one surface of the polysaccharide-treated membrane formed in (3) with an aqueous solution of an acid; (5) contacting the polysaccharide-treated membrane with an amine-functional alkoxysilane to form a polysaccharide hydrogel layer on the membrane. A treated microporous membrane prepared by the method is also provided.
[0006] Additionally provided is a method for treating a filter device, the filter device comprising a microporous membrane comprising an organic thermoplastic substrate; a finely divided particulate, substantially water-insoluble inorganic filler distributed throughout the substrate; a network of interconnected pores extending through the microporous membrane, and an acid-functional acrylic layer on at least one surface of the microporous membrane, wherein the acid-functional acrylic layer is bonded to the filler via siloxane functional groups. The method comprises, in sequence: (1) contacting at least one surface of the acid-functional acrylic layer on the microporous membrane with a dispersion comprising an amine-functional polysaccharide dispersed in an aqueous medium containing an organic acid to form a polysaccharide-treated membrane; (2) contacting at least one surface of the polysaccharide-treated membrane formed in (1) with an aqueous solution of an acid; and (3) contacting the polysaccharide-treated membrane with an amine-functional alkoxysilane to form a polysaccharide hydrogel layer on the membrane. The present invention also relates to a treated filter device prepared by the method.
[0007] The present invention further relates to a treated microporous membrane comprising: (1) a microporous membrane comprising an organic thermoplastic substrate; a finely divided particulate, substantially water-insoluble inorganic filler distributed throughout the substrate; and a network of interconnected pores communicating throughout the microporous membrane; (2) an acrylic layer on at least one surface of the microporous membrane, wherein the acrylic layer is bonded to the filler via siloxane functional groups; and (3) a hydrogel layer on at least one surface of the acrylic layer, wherein the hydrogel layer is formed from an amine-functional polysaccharide and an amine-functional alkoxysilane.
[0008] describe
[0009] For the purpose of the following detailed description, it should be understood that the present disclosure may take various alternative changes and step sequences, unless explicitly indicated to the contrary. In addition, except in any operating examples or where otherwise indicated, all numerals representing the amount of ingredients used in the specification and claims should be understood to be modified by the term "about" in all cases. Accordingly, unless otherwise indicated, the numerical parameters set forth in the following specification and the attached claims are approximate values that can be changed according to the desired properties to be obtained. At least, and not attempting to limit the application of the doctrine of equivalents to the scope of the claims, each numerical parameter should at least be interpreted according to the number of reported significant figures and by applying the usual rounding techniques.
[0010]
[0013] While the numerical ranges and parameters setting forth the broad scope of the present disclosure are approximations, the numerical values set forth in the specific examples are reported as precisely as possible. Any numerical value, however, inherently contains certain errors necessarily resulting from the standard deviation found in their respective testing measurements.
[0011] Furthermore, it should be understood that any numerical range described herein is intended to include all subranges subsumed therein. For example, a range of "1 to 10" is intended to include all subranges between (and including) the recited minimum value of 1 and the recited maximum value of 10, i.e., having a minimum value equal to or greater than 1 and a maximum value equal to or less than 10.
[0012] In the present application, unless otherwise specifically stated, the use of the singular includes the plural, and the plural encompasses the singular. Further, in the present application, unless otherwise specifically stated, the use of "a" or "an" means "at least one / kind". For example, "an" additive, "an" silica, etc. refer to one or more of these items. Moreover, as used herein, the term "polymer" means both prepolymers, oligomers, and homopolymers and copolymers. The term "resin" and "polymer" are used interchangeably.
[0013] As used herein, the transitional term "comprising" (and other similar terms, e.g., "containing" and "including") are "open ended" and when used with respect to compositions, methods, and their respective components, they are essential but not limiting inclusion of unspecified materials. The term "consisting essentially of refers to those components required for a given example, and allows for the presence of components that do not materially affect the properties or functional characteristics of that example. The term "consisting of" refers to compositions and methods that exclude any additional components not listed in the description of the example. Further note that the term "comprising" still encompasses the narrower terms "consisting essentially of" and "consisting of."
[0014] The present invention relates to a method of treating the surface of a microporous membrane comprising an organic thermoplastic substrate; a finely divided particulate, substantially water-insoluble inorganic filler distributed throughout the substrate; and a network of interconnected pores communicating throughout the microporous membrane. The method comprises the steps of: (1) contacting at least one surface of the film with a treatment composition to form a silane-treated film, the treatment composition comprising: (a) an acrylic polymer prepared from a mixture of vinyl monomers, the mixture of vinyl monomers comprising: (i) (meth) acrylic monomers and (ii) silane-functional acrylic monomers; (b) a sufficient amount of base to achieve at least 100% neutralization of the (meth) acrylic monomers, wherein the acrylic polymer is contacted with the filler present in the substrate; (2) subjecting the silane-treated film formed in (1) to conditions sufficient to achieve a condensation reaction between the filler and the acrylic polymer; (3) contacting at least one surface of the silane-treated film with a dispersion comprising an amine-functional polysaccharide dispersed in an aqueous medium containing an organic acid to form a polysaccharide-treated film; (4) contacting at least one surface of the polysaccharide-treated film formed in (3) with an aqueous solution of an acid; and (5) contacting the polysaccharide-treated film with an amine-functional alkoxysilane to form a polysaccharide hydrogel layer on the film.
[0015] As used herein, "microporous material" or "microporous membrane" or "microporous sheet" refers to a material having an interconnected network of pores, wherein the volume average diameter of the pores is 0.001 to 1.0 micrometers as measured as described below on an untreated, uncoated, unprinted ink, unimpregnated, and pre-bonded basis, and constitutes at least 5 volume % of the microporous material as described below.
[0016] As known in the art, the organic thermoplastic substrate may include any known polymeric materials, typically polyolefin materials. For example, the organic thermoplastic substrate may include polyolefins, polyetherketones, polyvinylidene fluoride (PVDF), polysulfones and / or polyethersulfones. In some cases, different polymers derived from at least one ethylenically unsaturated monomer may be used in combination with polyolefin polymers. Suitable examples of such polyolefin polymers may include, but are not limited to, polymers derived from ethylene, propylene and / or butene, such as polyethylene, polypropylene and polybutene. High-density and / or ultra-high molecular weight polyolefins known and defined in the art, such as high-density polyethylene (HDPE) are also suitable. The polyolefin substrate may also include copolymers, such as copolymers of ethylene and butene or copolymers of ethylene and propylene. It should be noted that the phrase "and / or" when used in a list is intended to cover alternative examples of each individual component and any combination of components included in the list. For example, the list "A, B and / or C" is intended to cover seven individual examples including A, or B, or C, or A+B, or A+C, or B+C, or A+B+C.
[0017] Non-limiting examples of ultra-high molecular weight (UHMW) polyolefins may include substantially linear UHMW polyethylene (PE) or polypropylene (PP). Because UHMW polyolefins are not thermosetting polymers with infinite molecular weight, they are technically classified as thermoplastic materials.
[0018] The ultra-high molecular weight polypropylene may include substantially linear ultra-high molecular weight isotactic polypropylene. Typically, such polymers have an isotacticity of at least 95%, such as at least 98%.
[0019] Although there is no particular upper limit on the intrinsic viscosity of the UHMW polyethylene, in a non-limiting example, the intrinsic viscosity can range from at least 6 dl / g, or at least 7 dl / g, or at least 18 dl / g, to at most 50 dl / g, or at most 45 dl / g, or at most 18 dl / g, or at most 16 dl / g. Thus, the intrinsic viscosity of the UHMW can be, for example, 6 to 50 dl / g, or 6 to 45 dl / g, or 6 to 18 dl / g, or 6 to 16 dl / g, or 7 to 50 dl / g, or 7 to 45 dl / g, or 7 to 18 dl / g, or 7 to 16 dl / g, or 18 to 50 dl / g, or 18 to 45 dl / g.
[0020] For purposes of this disclosure, intrinsic viscosity is determined by extrapolating to zero concentration the reduced or intrinsic viscosity of several dilute solutions of a UHMW polyolefin, wherein the solvent is freshly distilled decalin to which 0.2 wt. % of 3,5-di-tert-butyl-4-hydroxyhydrocinnamate neopentane tetraester [CAS Registry No. 6683-19-8] is added. The reduced or intrinsic viscosity of the UHMW polyolefin is determined using the relative viscosity obtained at 135° C. using an Ubbelohde No. 1 viscometer according to the general procedure of ASTM D 4020-81, except that several dilute solutions of varying concentrations are used.
[0021] The nominal molecular weight of UHMW polyethylene is empirically related to the intrinsic viscosity of the polymer according to the following equation:
[0022] M = 5.37 × 10 4 [η] 1.37
[0023] Where M is the nominal molecular weight and [η] is the intrinsic viscosity of the UHMW polyethylene expressed in deciliters per gram. Similarly, the nominal molecular weight of UHMW polypropylene is empirically related to the intrinsic viscosity of the polymer according to the following equation:
[0024] M=8.88×10 4 [η] 1.25
[0025] wherein M is the nominal molecular weight and [η] is the intrinsic viscosity of the UHMW polypropylene expressed in deciliter / gram.
[0026] A mixture of substantially linear ultra-high molecular weight polyethylene and lower molecular weight polyethylene can be used. For example, the intrinsic viscosity of the UHMW polyethylene is at least 10 deciliters / gram, and the ASTM D 1238-86 Condition E melt flow index of the lower molecular weight polyethylene is less than 50 grams / 10 minutes, such as less than 25 grams / 10 minutes, such as less than 15 grams / 10 minutes, and the ASTM D 1238-86 Condition F melt flow index is at least 0.1 grams / 10 minutes, such as at least 0.5 grams / 10 minutes, such as at least 1.0 grams / 10 minutes. The amount of the UHMW polyethylene used in this example (in weight percentage) is described in the 52nd row of the 1st column to the 18th row of the 2nd column of U.S. Patent No. 5,196,262, which is incorporated herein by reference. More specifically, the weight percentage of the UHMW polyethylene used is described with respect to FIG. 6 of U.S. Pat. No. 5,196,262; that is, with reference to polygons ABCDEF, GHCI, or JHCK of FIG. 6, which is incorporated herein by reference. For example, the weight percentage of the ultra-high molecular weight polyethylene in the total polyethylene of the substrate may be in the range of 3 to 60 weight percent, such as in the range of 10 to 48 weight percent,
[0027] Lower molecular weight polyethylene (LMWPE) has a lower nominal molecular weight than UHMW polyethylene. LMWPE is a thermoplastic material and many different types are known. One classification method is by density, expressed in grams per cubic centimeter and rounded to the nearest thousandth, according to ASTM D 1248-84 (reapproved in 1989). Non-limiting examples of density are shown in the table below.
[0028]
[0029] UHMWPE and LMWPE can together constitute at least 65% by weight of the polyolefin polymer of the microporous material, such as at least 85% by weight. Similarly, UHMWPE and LMWPE can together constitute substantially 100% by weight of the polyolefin polymer of the microporous material. In some examples, UHMWPE can constitute substantially 100% by weight (e.g., at least 99% by weight) of the polyolefin polymer of the microporous material.
[0030] Typically, the organic thermoplastic substrate may comprise a polyolefin comprising ultra-high molecular weight polyethylene, ultra-high molecular weight polypropylene, high density polyethylene, high density polypropylene, or mixtures thereof.
[0031] If desired, other thermoplastic organic polymers may also be present in the substrate of microporous material, as long as their presence does not substantially affect the properties of the microporous material substrate in an unfavorable manner. The amount of other thermoplastic polymers that may be present depends on the properties of this type of polymer. Non-limiting examples of thermoplastic organic polymers that may optionally be present in the substrate of microporous material include copolymers of low density polyethylene, high density polyethylene, poly(tetrafluoroethylene), polypropylene, ethylene and propylene, copolymers of ethylene and acrylic acid or copolymers of ethylene and methacrylic acid. If desired, all or part of the carboxyl groups of carboxyl-containing copolymers may be neutralized with sodium, zinc, etc. In general, microporous material comprises at least 70% by weight of UHMW polyolefins based on the weight of substrate. In non-limiting examples, substantially no other thermoplastic organic polymers are present in the substrate of microporous material.
[0032] The microporous membrane further comprises a finely divided, particulate, substantially water-insoluble, inorganic filler distributed throughout the substrate.
[0033] The inorganic filler may include any of a variety of inorganic fillers known in the art, as long as the filler is capable of condensing with the acrylic polymer present in the treatment composition applied to the membrane in (1). The filler should be finely divided and substantially insoluble in water to allow uniform distribution throughout the polyolefin polymer substrate during manufacture of the microporous material. Typically, the inorganic filler is selected from the group consisting of silicon dioxide, aluminum oxide, calcium oxide, zinc oxide, magnesium oxide, titanium oxide, zirconium oxide, and mixtures thereof.
[0034] The finely divided, substantially water-insoluble filler can be in the form of final particles, agglomerates of final particles, or a combination of the two. Using a laser diffraction particle size analyzer LS13320 from Beckman Coulter, at least 90% by weight of the filler used to prepare the microporous material has a total particle size in the range of 5 to 40 microns, as determined according to the manufacturer's instructions. The device is capable of measuring particle diameters as small as 0.04 microns, and generally, a laser with a wavelength of 750nm is used to measure particles with a diameter of 0.04mm to 2000mm. The particles scatter light in a pattern determined by their size, and a photodetector array detects and measures the scattered light. The photodetector is scanned and its output is converted into a digital value, which is then transmitted to a computer for calculation. Typically, at least 90% by weight of the filler has a total particle size in the range of 10 to 30 microns. During the processing of the ingredients used to prepare the microporous material, the size of the filler agglomerates can be reduced. Therefore, the total particle size distribution in the microporous material can be smaller than the total particle size distribution of the raw material filler itself.
[0035] As previously mentioned, the filler particles are substantially insoluble in water and may also be substantially insoluble in any organic processing liquid used to prepare the microporous material. In other words, the composition of the filler particles facilitates retention of the filler in the microporous material.
[0036] In addition to fillers, other finely divided particulate, substantially water-insoluble materials may optionally be used. Non-limiting examples of such optional materials may include carbon black, charcoal, graphite, iron oxide, copper oxide, antimony oxide, molybdenum disulfide, zinc sulfide, barium sulfate, strontium sulfate, calcium carbonate, or magnesium carbonate. In a non-limiting example, silica and any one or more of the aforementioned optional filler materials may constitute the filler.
[0037] The filler typically has a high surface area, allowing the filler to carry a large amount of processing plasticizer used to form the microporous material. The surface area of the filler particles can be in the range of at least 20 square meters per gram, or at least 25 square meters per gram, to at most 900 square meters per gram, or at most 850 square meters per gram; for example, 20 to 900 square meters per gram, or 20 to 850 square meters per gram, or 25 to 900 square meters per gram, or 25 to 850 square meters per gram. As determined by the Brunaue, Emmett, Teller (BET) method according to ASTM C 819-77 using nitrogen as the adsorbate, but instead venting the system and sample at 130°C for one hour. Prior to nitrogen adsorption, the filler sample was dried by heating to 160°C in flowing nitrogen (PS) for 1 hour.
[0038] In a specific example, the inorganic filler comprises silica, such as precipitated silica, silica gel, or fumed silica.
[0039] Silica gel is usually produced commercially by acidifying an aqueous solution of a soluble metal silicate (e.g. sodium silicate) with an acid at low pH. The acid used is usually a strong mineral acid such as sulfuric acid or hydrochloric acid, but carbon dioxide can also be used. Due to the substantial lack of density difference between the gel phase and the surrounding liquid phase and the low viscosity, the gel phase does not settle, that is, it does not precipitate. Silica gel can therefore be described as a non-precipitating, coherent, rigid three-dimensional network of continuous particles of colloidal amorphous silicon dioxide. The state of subdivision ranges from large solid blocks to submicroscopic particles, and the degree of hydration ranges from nearly anhydrous silica to soft gel blocks containing 100 parts of water per part of silica by weight.
[0040] Commercially, precipitated silica is usually produced by mixing an aqueous solution of a soluble metal silicate (usually an alkali metal silicate, such as sodium silicate) with an acid so that colloidal particles of silica will grow in a weakly alkaline solution and be condensed by the alkali metal ions of the resulting soluble alkali metal salt. Various acids can be used, including but not limited to inorganic acids. Non-limiting examples of acids that can be used include hydrochloric acid and sulfuric acid, but carbon dioxide can also be used to produce precipitated silica. In the absence of a coagulant, silica will not precipitate from the solution at any pH value. In a non-limiting example, the coagulant used to achieve silica precipitation can be a soluble alkali metal salt produced during the formation of colloidal silica particles, or it can be an added electrolyte, such as a soluble inorganic salt or organic salt, or it may be a combination of the two.
[0041] Precipitated silica can be described as precipitated agglomerates of colloidal amorphous silica final particles, which at no time during the preparation are present in the form of a macroscopic gel. The size and degree of hydration of the agglomerates may vary greatly. Precipitated silica powder differs from crushed silica gel in that it generally has a more open structure, i.e. a higher specific pore volume, than silica gel. However, the specific surface area of precipitated silica measured by the Brunaue, Emmett, Teller (BET) method using nitrogen as the adsorbate is generally lower than that of silica gel.
[0042] Many different precipitated silicas can be used as fillers for preparing microporous materials. Precipitated silica is a well-known commercial material, and its production method is described in detail in many U.S. patents, including U.S. Patent Nos. 2,940,830 and 4,681,750. As measured by transmission electron microscopy, the average final particle size of the precipitated silica used (whether the final particles are agglomerated or not) is generally less than 0.1 micron, such as less than 0.05 micron or less than 0.03 micron. Non-limiting examples of suitable precipitated silicas include those sold by PPG (Pittsburgh, Pennsylvania) under the trade name HI-SIL.
[0043] Inorganic filler particles can constitute at least 10% by weight of the microporous membrane, or at least 25% by weight, or at least 30% by weight, or at least 40% by weight, or at least 50% by weight, or at least 60% by weight, and up to 90% by weight, or up to 85% by weight of the microporous membrane. For example, such filler particles can account for 25 to 90% by weight, or 25 to 85% by weight, or 30 to 90% by weight, or 30 to 85% by weight, or 40 to 90% by weight, or 40 to 85% by weight, or 50 to 90% by weight, or 50 to 85% by weight, or 60 to 90% by weight, or 60 to 85% by weight of the microporous membrane. Filler is usually present in the microporous membrane in an amount ranging from 50% by weight to 85% by weight of the microporous membrane. Typically, the weight ratio of filler to polyolefin in the microporous material ranges from 0.5:1 to 10:1, such as 1.7:1 to 3.5:1. Alternatively, the weight ratio of filler to polyolefin in the microporous material may be greater than 4: 1. It is contemplated that higher levels of filler may be used because such levels of filler will provide a higher surface area available for condensation reaction with the treatment composition.
[0044] The microporous materials used in the disclosed membranes further comprise a network of interconnected pores communicating throughout the microporous material.
[0045] Based on the situation of no treatment, no coating or no impregnant, such pores can account for at least 5 volume %, or at least 15 volume %, or at least 20 volume %, or at least 25 volume %, or at least 35 volume %, or at least 45 volume %, and at most 95 volume %, or at most 75 volume %. Therefore, such pores can account for 5 to 95 volume %, or 15 to 95 volume %, or 20 to 95 volume %, or 25 to 95 volume %, or 35 to 95 volume %, or 45 to 95 volume %, or 5 to 70 volume %, or 15 to 70 volume %, or 20 to 70 volume %, or 25 to 70 volume %, or 35 to 70 volume %, or 45 to 70 volume %. Typically, such pores account for at least 35 volume %, or even at least 45 volume % of the volume of the microporous material. This high porosity provides a higher surface area in the entire microporous material, which in turn helps to remove pollutants from the fluid flow and the higher flow rate of the fluid flow through the membrane.
[0046] As used herein and in the claims, the porosity (also referred to as void volume) of a microporous material, expressed as volume %, is determined according to the following equation:
[0047] Porosity = 100[1-d 1 / d 2 ]
[0048] where d 1 is the density of the sample, which is determined from the sample volume determined by measuring the sample dimensions and the sample weight, and d 2is the density of the solid portion of the sample, which is determined from the sample weight and the volume of the solid portion of the sample.The volume of the solid portion of the sample was determined using a Quantachrome stereodensitometer (Quantachrom Corporation, Boynton Beach, FL) according to the accompanying operating manual.
[0049] Porosity can also be measured using a Gurley Densitometer Model 4340 manufactured by GPI Gurley Precision Instruments (Troy, New York). The reported porosity value is a measure of the airflow rate through the sample or its resistance to airflow through the sample. The unit of measurement for this method is the "Gurley second," which represents the time (in seconds) required to pass 100cc of air through an area of 1 square inch using a pressure differential of 4.88 inches of water column. Lower values are equivalent to less resistance to airflow (allowing more air to pass freely). The measurement is completed using the procedure listed in the manual for the Model 4340 Automatic Densitometer.
[0050] The volume average diameter of the pores of the microporous material can be determined by mercury porosimetry using an Autopore III porosimeter (Micromeritics, Inc., Norcross, Georgia) according to the accompanying operating manual. The volume average pore radius of a single scan is automatically determined by the porosimeter. While operating the porosimeter, scans are performed in the high pressure range (from 138 kPa absolute to 227 MPa absolute). If about 2% or less of the total mercury injected volume (intruded volume) occurs at the low end of the high pressure range (138 to 250 kPa absolute), the volume average pore diameter is taken as twice the volume average pore radius determined by the porosimeter. Otherwise, an additional scan is performed in the low pressure range (7 to 165 kPa absolute) and the volume average pore diameter is calculated according to the following formula:
[0051] d=2[v 1 r 1 / w 1 +v 2 r 2 / w 2 ] / [v 1 / w 1 +v 2 / w 2 ]
[0052] Where d is the volume average pore diameter, v 1 is the total volume of mercury injected within the high pressure range, v 2 is the total volume of mercury injected in the low pressure range, r 1 is the volume average pore radius determined by high pressure scanning, r2 is the volume average pore radius determined by low pressure scanning, w 1 is the weight of the sample subjected to the high-voltage scan, w 2 is the weight of the sample subjected to the low pressure scan.
[0053] During the determination of the volume average pore diameter by the above process, the maximum pore radius detected is sometimes recorded. This is taken from the low pressure range scan (if run); otherwise, it is taken from the high pressure range scan. The maximum pore diameter is twice the maximum pore radius. Since some production or processing steps, such as coating processes, printing processes, impregnation processes and / or bonding processes, may result in the filling of at least some of the pores of the microporous material, and since some of these processes irreversibly compress the microporous material, the parameters of the microporous material regarding porosity, volume average diameter of pores and maximum pore diameter are determined before applying one or more such production or processing steps.
[0054] In order to prepare the disclosed microporous material, filler, organic thermoplastic substrate, such as polyolefin polymer (usually in solid form, such as powder or pellets), processing plasticizer and small amounts of lubricant and antioxidant are mixed until a substantially uniform mixture is obtained. The weight ratio of filler to polymer used to form the mixture is substantially the same as the weight ratio of the microporous material substrate to be produced. The mixture is introduced into the heating barrel of a screw extruder together with additional processing plasticizer. Connected to the extruder is a mold, such as a tableting mold, to form the desired final shape.
[0055] In an exemplary manufacturing process, when the material is formed into a sheet or film, the continuous sheet or film formed by the mold is conveyed to a pair of cooperating heated calendering rollers to form a continuous sheet with a smaller thickness than the continuous sheet leaving the mold. The final thickness may depend on the desired end use. The thickness range of the microporous material can be 0.7 to 18 mils (17.8 to 457.2 microns), for example 0.7 to 15 mils (17.8 to 381 microns), or 1 to 10 mils (25.4 to 254 microns), or 5 to 10 mils (127 to 254 microns).
[0056] Optionally, the sheet leaving the calendering roller can then be stretched to above the elastic limit in at least one stretching direction. Alternatively, the stretching can be carried out during calendering, during withdrawal from the tableting die, or immediately after withdrawal from the tableting die, or multiple times during the manufacturing process. The stretching can be carried out before extraction, after extraction, or both. In addition, the stretching can occur during the application of the pretreatment composition and / or the treatment composition, as described in more detail below. The stretched microporous material substrate can be prepared by stretching the intermediate product to above the elastic limit in at least one stretching direction. Generally, the stretching ratio is at least 1.2. In many cases, the stretching ratio is at least 1.5. Generally at least 2. Typically, the stretching ratio is in the range of 1.2 to 15. Often, the stretching ratio is in the range of 1.5 to 10. Generally, the stretching ratio is in the range of 2 to 6.
[0057] The temperature at which the stretching is completed can vary widely. Stretching can be completed at ambient room temperature, but elevated temperatures are typically used. The intermediate product can be heated by any of a variety of techniques before, during, and / or after stretching. Examples of these techniques include radiant heating, such as heating provided by electric or gas-fired infrared heaters; convection heating, such as heating provided by recirculating hot air; and conductive heating, such as heating provided by contact with heated rollers. The temperature measured for temperature control purposes can vary depending on the equipment used and personal preferences. For example, a temperature measuring device can be placed to determine the surface temperature of an infrared heater, the internal temperature of an infrared heater, the air temperature at a point between the infrared heater and the intermediate product, the temperature of circulating hot air at a point within the device, the temperature of hot air entering or leaving the device, the surface temperature of the rollers used during the stretching process, the temperature of a heat transfer fluid entering or leaving such rollers, or the surface temperature of the film. In general, one or more temperatures are controlled so that the intermediate product is stretched approximately uniformly, so that the variation in the film thickness of the stretched microporous material (if any) is within acceptable limits, and so that the amount of stretched microporous material outside these limits is acceptably low. Obviously, the temperatures used for control purposes may or may not be close to the temperatures of the intermediate products themselves, as they depend on the nature of the equipment used, the location of the temperature measuring device, and the characteristics of the substance or object whose temperature is being measured.
[0058] Given the location of the heating device and the line speeds typically employed during stretching, varying temperature gradients may or may not exist across the thickness of the intermediate product. Furthermore, due to such line speeds, measuring these temperature gradients is impractical. When gradients of varying temperatures occur, their presence makes quoting a single film temperature unreasonable. Therefore, a measurable film surface temperature is best suited for characterizing the thermal condition of the intermediate product.
[0059] The film surface temperatures at which stretching is completed may vary widely, but in general they are such that the intermediate product is approximately uniformly stretched, as described above. In most cases, the film surface temperature during stretching is in the range of 20° C. to 220° C. Typically, such temperatures are in the range of 50° C. to 200° C., such as 75° C. to 180° C.
[0060] As required, stretching can be completed in a single step or multiple steps. For example, when the intermediate product will be stretched in a single direction (uniaxial stretching), stretching can be completed by a single stretching step or a series of stretching steps until the desired final stretch ratio is obtained. Similarly, when the intermediate product is to be stretched in two directions (biaxial stretching), stretching can be carried out by a single biaxial stretching step or a series of biaxial stretching steps until the desired final stretch ratio is obtained. Biaxial stretching can also be achieved by a series of steps of one or more uniaxial stretching steps in one direction and one or more uniaxial stretching steps in another direction. The biaxial stretching step and the uniaxial stretching step in which the intermediate product is stretched simultaneously in two directions can be carried out in sequence in any order. It can be considered to stretch in more than two directions. It can be seen that the various arrangements of steps are quite a lot. Other steps, such as cooling, heating, sintering, annealing, winding, unwinding, etc., can be optionally included in the whole process as required.
[0061] Various types of stretching equipment are well known and can be used to complete the stretching of the intermediate product. Uniaxial stretching is usually achieved by stretching between two rollers, wherein the second roller or downstream roller rotates at a greater peripheral speed than the first roller or upstream roller. Uniaxial stretching can also be done on a standard tenter. Biaxial stretching can be achieved by stretching simultaneously in two different directions on a tenter. However, more commonly, biaxial stretching is achieved by first uniaxially stretching between two differentially rotating rollers as described above, and then using a tenter to stretch uniaxially in different directions or by using a tenter to perform biaxial stretching. The most common type of biaxial stretching is that the two stretching directions are approximately at right angles to each other. In most cases where a continuous sheet is stretched, one stretching direction is at least approximately parallel to the long axis (machine direction) of the sheet, and the other stretching direction is at least approximately perpendicular to the machine direction and in the plane of the sheet (transverse direction).
[0062] Stretching the sheet before extracting the processing plasticizer can result in a thinner film with a larger pore size than conventionally processed microporous materials. It is also believed that stretching the sheet before extracting the processing plasticizer can minimize thermal shrinkage after processing. It should also be noted that stretching of the microporous membrane can be performed before, during, or after applying the pretreatment composition, and / or at any time point before, during, or after applying the treatment composition (as described below). During the treatment process, stretching of the microporous membrane can occur once or multiple times.
[0063] The product enters a first extraction zone where the processing plasticizer is substantially removed by extraction with an organic liquid which is a good solvent for the processing plasticizer, a poor solvent for the organic polymer, and which is more volatile than the processing plasticizer. Typically, but not necessarily, both the processing plasticizer and the organic extract are substantially immiscible with water. The product then enters a second extraction zone where the residual organic extract is substantially removed by steam and / or water. The product is then passed through a forced air dryer to substantially remove the residual water and the remaining residual organic extract. When the microporous material is in sheet form, it can be transferred from the dryer to a take-up roll.
[0064] Processing plasticizers have little solubilizing effect on thermoplastic organic polymers at 60°C, only moderate solvating effect at high temperatures around 100°C, and significant solvating effect at high temperatures around 200°C. It is liquid at room temperature and is usually a processing oil, such as paraffinic oil, naphthenic oil or aromatic oil. Suitable processing oils include those that meet the requirements of ASTM D2226-82, 103 and 104. Oils with a pour point of less than 22°C or less than 10°C according to ASTM D 97-66 (reapproved in 1978) are most commonly used. Examples of suitable oils include SHELLFLEX 412 and SHELLFLEX 371 oils (Shell Oil Co., Houston, Texas), which are solvent-refined and hydrotreated oils derived from naphthenic crude oils. It is expected that other materials, including phthalate plasticizers such as dibutyl phthalate, bis(2-ethylhexyl) phthalate, diisodecyl phthalate, dicyclohexyl phthalate, butyl benzyl phthalate, and ditridecyl phthalate will function satisfactorily as processing plasticizers.
[0065] There are many organic extracts that can be used in the microporous membrane manufacturing process. Examples of suitable organic extracts include, but are not limited to, 1,1,2-trichloroethylene; perchloroethylene; 1,2-dichloroethane; 1,1,1-trichloroethane; 1,1,2-trichloroethane; dichloromethane; chloroform; 1,1,2-trichloro-1,2,2-trifluoroethane; isopropanol; diethyl ether; acetone; hexane; heptane and toluene. One or more azeotropes of halogenated hydrocarbons selected from trans-1,2-dichloroethylene, 1,1,1,2,2,3,4,5,5,5-decafluoropentane and / or 1,1,1,3,3-pentafluorobutane may also be used. Such materials are commercially available as VERTREL MCA (binary azeotrope of 1,1,1,2,2,3,4,5,5,5-dihydrodecafluoropentane and trans-1,2-dichloroethylene: 62% / 38%) and VERTREL CCA (ternary azeotrope of 1,1,1,2,2,3,4,5,5,5-dihydrodecafluoropentane, 1,1,1,3,3-pentafluorobutane, and trans-1,2-dichloroethylene: 33% / 28% / 39%); VERTREL SDG (80-83% trans-1,2-dichloroethylene, 17-20% hydrofluorocarbon mixture), all available from MicroCare Corporation (New Britain, Connecticut).
[0066] In the above-mentioned method for making microporous membranes, extrusion and calendering are facilitated when the filler carries a large amount of processing plasticizer. The ability of the filler particles to absorb and retain the processing plasticizer is a function of the filler surface area. Therefore, the filler generally has a high surface area as described above. Since it is desirable to substantially retain the filler in the microporous material substrate, when the microporous material substrate is produced by the above-mentioned method, the filler should be substantially insoluble in the processing plasticizer and substantially insoluble in the organic extract. The residual processing plasticizer content is generally less than 15% by weight of the resulting microporous material, and by using the same or different organic extract for additional extraction, the content can even be further reduced to a level of, for example, less than 5% by weight. The resulting microporous material can be further processed according to the desired application.
[0067] As previously described, the method for treating the surface of a microporous membrane (as described above) comprises (1) contacting at least one surface of the membrane with a treatment composition comprising: (a) an acrylic polymer prepared from a vinyl mixture comprising: (i) a (meth) acrylic monomer and (ii) a silane-functional acrylic monomer; and optionally, (b) a base. Additionally, the acrylic polymer is contacted with a filler present in the substrate. The method further comprises: (2) subjecting the membrane of (1) to conditions sufficient to effect a condensation reaction between the inorganic filler and the acrylic polymer of the treatment composition.
[0068] The treatment composition for treating the surface of the microporous membrane comprises (a) an acrylic polymer and optionally (b) a base. The treatment composition may further comprise (c) at least one of poly(N-vinylpyrrolidone) or polyoxazoline.
[0069] The treatment composition may be a solution in which the components of the treatment composition (e.g., acrylic polymer (a), optional base (b), and optionally at least one of poly(N-vinylpyrrolidone) or polyoxazoline (c)) are dissolved in a solvent such as an alkyl alcohol or a volatile ketone. Particularly suitable solvents include those having a boiling point below 120°C, examples include methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, 2-butanol, acetone, methyl ethyl ketone, and methyl isobutyl ketone. Note that when the solution is not aqueous, base (b) is generally not necessary.
[0070] Alternatively, the treatment composition can be an aqueous treatment composition, wherein the components of the treatment composition (e.g., acrylic polymer (a), base (b), optionally at least one of poly(N-vinylpyrrolidone) or polyoxazoline (c)) are dispersed in an aqueous medium. When present, the base is typically used in sufficient amounts to achieve at least 100% neutralization of the (meth)acrylic acid monomer. As used herein, "aqueous medium" refers to a liquid medium that contains at least 50% by weight of water, based on the total weight of the liquid medium. Such aqueous liquid media may, for example, contain at least 60% by weight of water, or at least 70% by weight of water, or at least 80% by weight of water, or at least 90% by weight of water, or at least 95% by weight of water, or 100% by weight of water, based on the total weight of the liquid medium. If present, less than 50% by weight of the solvent constituting the liquid medium includes an organic solvent. Non-limiting examples of suitable organic solvents include polar organic solvents. By definition, a molecule may be "polar" when there is an unequal sharing of electrons between the two atoms of a diatomic molecule, or when there is an overall dipole in the molecule due to an asymmetric arrangement of polar bonds in more complex molecules. Examples of polar solvents include protic organic solvents such as glycols, alcohols, glycol ether alcohols, volatile ketones, glycol diethers, esters, and diesters. Other non-limiting examples of organic solvents include aromatic and aliphatic hydrocarbons. The treatment composition may have a pH>7.
[0071] Acrylic polymer (a) can be prepared from a mixture of vinyl monomers. Vinyl monomers generally include (i) (meth) acrylic monomers and (ii) silane-functional acrylic monomers. Vinyl monomers may include (iii) N-vinyl pyrrolidone. (Meth) acrylic monomers (i) may be present in an amount of at least 2 wt %, or at least 5 wt %, and at most 20 wt %, or at most 10 wt %, for example, 2-20 wt %, or 5-20 wt %, or 2-10 wt %, or 5-10 wt %, based on the total weight of the vinyl monomers. The silane-functional acrylic monomer (ii) can be present in an amount of at least 10 wt%, or at least 20 wt%, or at least 40 wt%, and up to 80 wt%, or up to 70 wt%, or up to 60 wt%; or up to 55 wt%; for example, 10-80 wt%, or 10-70 wt%, or 10-60 wt%, or 10-55 wt%, or 20-80 wt%, or 20-70 wt%, or 20-60 wt%, or 20-55 wt%, or 40-80 wt%, or 40-70 wt%, or 40-60 wt%, or 40-55 wt%, based on the total weight of the vinyl monomer. When present, N-vinyl pyrrolidone (iii) may be present in an amount of at least 1 wt%, or at least 5 wt%, and up to 60 wt%; or up to 40 wt%; or up to 25 wt%; or up to 15 wt%; for example, 1-60 wt%, or 1-40 wt%, or 1-25 wt%, or 1-15 wt%, or 5-60 wt%, or 5-40 wt%, or 5-25 wt%, or 5-15 wt%, based on the total weight of the vinyl monomer.
[0072] Other vinyl monomers may be present to prepare the acrylic polymer (a), and non-limiting examples may optionally include: methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, hydroxyethyl (meth)acrylate, hydroxybutyl (meth)acrylate, hydroxypropyl (meth)acrylate, styrene, acrylamide, alkyl substituted acrylamide, 2-ethylhexyl (meth)acrylate, isobornyl (meth)acrylate, cyclohexyl (meth)acrylate, lauryl (meth)acrylate, substituted styrenes, maleic anhydride, or combinations thereof.
[0073] As used herein, the term "acrylic acid" polymer refers to those polymers obtained by polymerization of one or more ethylenically unsaturated polymerizable materials well known to those skilled in the art. Suitable acrylic acid polymers for use can be prepared by any of a variety of methods, as will be understood by those skilled in the art. In some instances, such acrylic acid polymers are prepared by addition polymerization of different unsaturated polymerizable materials, at least one of which is (ii) a silane-functional acrylic acid monomer. The result of this polymerization is an acrylic acid polymer comprising a hydrolyzable silane functional group. Examples of hydrolyzable silane groups include, but are not limited to, groups with a Si-Xn structure (wherein n is an integer with a value in the range of 1 to 3 and X is selected from chlorine, bromine, iodine, alkoxy esters and / or acyloxy esters).
[0074] The (meth)acrylic acid monomer (i) may include acrylic acid, methacrylic acid, or a combination thereof.
[0075] Non-limiting examples of silane-functional acrylic monomers (ii) include: ethylenically unsaturated alkoxysilanes and ethylenically unsaturated acyloxysilanes, more specific examples of which include acrylalkoxysilanes, such as γ-acryloxypropyltrimethoxysilane and γ-acryloxypropyltriethoxysilane, and methacrylalkoxysilanes, such as γ-methacryloxypropyltrimethoxysilane, γ-methacryloxypropyltriethoxysilane and γ-methacryloxypropyltri-(2-methoxyethoxy)silane; acyloxysilanes, including, for example, acrylacetoxysilane, methacrylacetoxysilane and ethylenically unsaturated acetoxysilanes, such as acrylpropyltriacetoxysilane and methacrylpropyltriacetoxysilane. In certain instances, it may be desirable to use monomers that will produce acrylic polymers upon addition polymerization in which the Si atom of the resulting hydrolyzable silyl group is separated from the polymer backbone by at least two atoms. A non-limiting commercial example of a suitable (ii) silane-functional acrylic monomer includes SILQUEST A-174, available from Momentive Performance Materials (Waterford, NY).
[0076] The weight average molecular weight (M w , g / mol or Da) can be at least 10,000 Da, or at least 12,000 Da, and up to 35,000, such as up to 30,000, or up to 25,000, or up to 20,000, or up to 16,000, or up to 15,000 Da. Thus, M wThe molecular weight of the present invention may be in the range of 10,000-35,000, or 10,000-30,000, or 10,000-25,000, or 10,000-20,000, or 10,000-16,000, or 10,000-15,000, or 12,000-35,000, or 12,000-30,000, or 12,000-25,000, or 12,000-20,000, or 12,000-16,000, or 12,000-15,000 Da. As reported herein, M w M is measured by gel permeation chromatography according to ASTM D6579-11 using polystyrene standards (gel permeation chromatography for characterization of polymer samples was performed using a Waters 2695 separation module with a Waters 2414 differential refractometer (RI detector); tetrahydrofuran (THF) was used as the eluent at a flow rate of 1 ml / min, and two PLgelMixed-C (300×7.5 mm) columns were used for separation; the M of a polymer sample can be measured by gel permeation chromatography relative to a linear polystyrene standard of 800 to 900,000 Da). w ).
[0077] Once the treatment composition is applied to the microporous membrane, the acrylic polymer (a) may be contacted with the filler present in the substrate such that the membrane may be subjected to conditions sufficient to effect a condensation reaction between the filler and the acrylic polymer (a).
[0078] In some non-limiting examples, the acrylic polymer (a) can comprise 90-100% by weight of the solids in the treatment composition.
[0079] Base (b) may include any compound capable of neutralizing (meth)acrylic monomer (a). Base (b) may be present in an amount that at least partially neutralizes (meth)acrylic monomer (i). For example, base (b) may be included in an amount sufficient to neutralize at least 50%, or at least 75%, or at least 100% of (i) (meth)acrylic monomer. For example, base (b) may be included in an amount sufficient to neutralize up to 250%, or up to 300%, or up to 400% of (meth)acrylic monomer (i). Sufficient base (b) may be included in the treatment composition to neutralize 100%-300%, such as 110-250%, or such as 150%-200% of (meth)acrylic monomer (i).
[0080] Non-limiting examples of base (b) include amines (e.g., dimethylethanolamine, dibutylamine, diisopropylamine, amine-functional alkoxysilanes), sodium hydroxide, ammonium hydroxide, etc. The amine may include a tertiary amine. Ammonium hydroxide, dimethylethanolamine, dibutylamine, and diisopropylamine are particularly suitable.
[0081] The optional poly(N-vinylpyrrolidone) or polyoxazoline (c) may include polyalkyloxazolines such as poly(2-ethyl-2-oxazoline), poly(2-methyl-2-oxazoline) and poly(2-methyl / ethyl-2-oxazoline); and / or poly(N-vinylpyrrolidone).
[0082] In some non-limiting examples, the poly(N-vinylpyrrolidone) or polyoxazoline (c) may comprise 1-20 wt % of the solids in the treatment composition.
[0083] Before contacting the treatment composition with at least one surface of the microporous membrane, the microporous membrane may be pretreated with a pretreatment composition. The surface of the microporous membrane may be pretreated by contacting with a hydrophilic polymer. "Hydrophilic" means that the polymer has a polar property and has a tendency to interact with, be miscible with, or be dissolved by water and other polar substances. The hydrophilic polymer (c) may include any hydrophilic polymer from section
[0090] of U.S. Patent Application Publication No. 2014 / 0069862, such as one or more polyoxazolines, including polyalkyloxazolines, such as poly(2-ethyl-2-oxazoline), poly(2-methyl-2-oxazoline) and poly(2-methyl / ethyl-2-oxazoline); triblock copolymers based on poly(ethylene glycol)-poly(propylene glycol)-poly(ethylene glycol); polyethylene imine; polyamide; polyethylene oxide or its derivatives; polyethylene oxide; polyethylene glycol; poly(N-vinyl pyrrolidone ); polyacrylic acid; polymethacrylic acid; polyethylene glycol derivatives; polypropylene oxide or its derivatives; copolymers of poly(ethylene glycol) and polyethylene oxide; polyvinyl alcohol; ethylene vinyl acetate; cellulose or its derivatives; polyimide; hydrogels such as collagen, polypeptides, guar gum and pectin; polypeptides; poly(meth)acrylates such as poly(2-hydroxyethyl methacrylate); poly(meth)acrylamide; polysaccharides such as chitosan; zwitterionic polymers such as poly(phosphorylcholine) derivatives, polysulfobetaines and polycarbobetaines; polyampholytes, or polyethyleneimine. The pretreated microporous membrane may be dried prior to contact with the treatment composition, or the treatment composition may be contacted with the wetted surface after the pretreatment. In some non-limiting examples, the surface of the microporous membrane may be contacted with a hydrophilic polymer after contact with the treatment composition, so that the hydrophilic polymer is used as a post-treatment composition. This may be in addition to, or instead of, using a hydrophilic polymer as a pretreatment composition.
[0084] The pretreatment composition and / or treatment composition can (1) be contacted with at least one surface of the microporous membrane by any application method known in the art. For example, the treatment composition can be applied to at least one surface of the microporous membrane by immersion, spraying, dipping and / or flowing or some application technique. The treatment composition can be applied after plasticizer extraction and before, during or after any of the aforementioned stretching steps. Alternatively, stretching can be delayed until the treatment composition is applied.
[0085] The treatment composition can be applied to the membrane dry or pre-wetted.
[0086] When the treatment composition is applied to at least one surface of the microporous membrane in (1), a silane-treated membrane is formed. The silane-treated membrane (2) of (1) is then subjected to conditions sufficient to effect a condensation reaction between the inorganic filler (e.g., functional groups present on its surface) and the acrylic polymer (a) (e.g., via silane groups present in the residues of the silane-functional acrylic monomer (ii)). Such reaction conditions are discussed in more detail below.
[0087] The conditions (2) sufficient for the condensation reaction may include drying as described below. The conditions (2) sufficient for the condensation reaction may include adjusting the pH to a range of 4 to 7, for example by washing the membrane with water (eg, deionized or distilled water) or a dilute aqueous acid solution.
[0088] In addition, the treatment composition can be applied in multiple steps. That is, the microporous membrane can be applied with the treatment composition in (1) one or more times. In addition, the treatment compositions applied in such multiple step applications can be the same or different compositions, as long as each composition contains at least one acrylic polymer (a). It should also be noted that any of the aforementioned treatment compositions suitable for application to the microporous membrane of (1) according to the disclosed method can further contain at least one nonionic surfactant and / or anionic surfactant and / or rheology modifier, as described immediately below.
[0089] Non-limiting examples of suitable anionic surfactants for the treatment compositions used in the disclosed methods can include, but are not limited to, sodium stearate, ammonium stearate, ammonium cocoate, sodium laurate, sodium cocoyl sarcosinate, sodium lauroyl sarcosinate, sodium tallow soap, sodium coconut soap, sodium myristoyl sarcosinate, dioctyl sodium sulfosuccinate, or some combination thereof.
[0090] Rheology modifiers may be pseudoplastic or thixotropic in nature. Non-limiting examples of suitable rheology modifiers for the treatment compositions used in the disclosed methods may include, but are not limited to, cationic quaternary amine compounds coupled to propylene glycol (e.g., DISPERSOGEN SPS from Clariant, Muttenz, Switzerland), aqueous dispersions of acrylic acid copolymers (e.g., RHEOTECH 4800 from Arkema Group, Colombes, France), anionic aqueous solutions of sodium polyacrylate (e.g., ALCOGUM 296-W from AkzoNobel, Amsterdam, The Netherlands, or some combination thereof.
[0091] Non-limiting examples of suitable nonionic surfactants for the treatment compositions used in the disclosed methods may include, but are not limited to, polyethylene oxide alkyl ethers, wherein the alkyl group may be linear or branched with a chain length of C6 to C22; polyethylene oxide alkyl esters, wherein the alkyl group may be linear or branched with a chain length of C6 to C22; organic amines having a C6 to C22 branched or linear carbon chain of the general formula R*NR'R", wherein R* may be a C8 to C22 alkyl group and R' and R" may each independently be H or a C1 to C4 alkyl group, such that the molecule may be substantially soluble in water or substantially emulsifiable in water, such as octadecylamine; tertiary amines having a carbon chain of C6 to C22; polyethyleneimines; polyacrylamides; alcohols and glycols, polyvinyl alcohol, having a C6 to C22 linear or branched alkyl group that may form an ester bond (-SiOC-); and mixtures thereof.
[0092] The nonionic surfactant can also be selected from the following: polyoxyalkylene ethers, such as polypropylene oxide ethers or polyethylene oxide ethers, such as but not limited to hexaethylene glycol monododecyl ether, hexaethylene glycol monohexadecyl ether, hexaethylene glycol monotetradecyl ether, hexaethylene glycol monooctadecyl ether, heptaethylene glycol monododecyl ether, heptaethylene glycol monohexadecyl ether, heptaethylene glycol monotetradecyl ether, heptaethylene glycol monooctadecyl ether, nineethylene glycol monododecyl ether, eightethylene glycol monododecyl ether; polyoxyalkylene esters, such as polypropylene oxide esters or polyethylene oxide esters, such as but not limited to hexaethylene glycol monododecyl ester, hexaethylene glycol monohexadecyl ester, hexaethylene glycol monotetradecyl ether, heptaethylene glycol monooctadecyl ether, heptaethylene glycol monododecyl ether, heptaethylene glycol mono hexadecyl ester, heptaethylene glycol monotetradecyl ester, heptaethylene glycol monooctadecyl ester, nonaethylene glycol monododecyl ester, octaethylene glycol monododecyl ester; polysorbates, such as polyoxyethylene sorbitan monofatty acid esters, including but not limited to polyoxyethylene sorbitan monopalmitate, polyoxyethylene sorbitan monooleate, polyoxyethylene sorbitan monostearate, polyoxyethylene sorbitan difatty acid esters, such as polyoxyethylene sorbitan dipalmitate, polyoxyethylene sorbitan dioleate, polyoxyethylene sorbitan distearate, polyoxyethylene sorbitan monopalmitate monooleate, polyoxyethylene sorbitan trifatty acid esters, such as but not limited to polyoxyethylene sorbitan tristearate; or mixtures thereof.
[0093] In one particular example, the treatment composition may include a nonionic surfactant selected from the group consisting of block copolymers based on poly(ethylene glycol), such as block copolymers of poly(propylene glycol) and poly(ethylene glycol), (e.g., triblock copolymer PLURONIC 17R2, commercially available from BASF Corporation, Ludwigshafen, Germany); cetearyl alcohol; polyethylene glycol and its derivatives, such as polyoxyethylene octylphenyl ether; polyalkylene glycols; cetyl alcohol; cocamide monoethanolamine or diethanolamine; decyl glucoside; octylphenoxypolyethoxyethanol; isocetyl alcohol; lauryl glucoside; glyceryl monolaurate; fatty alcohol polyethylene glycol ethers; polyethylene glycol ethers; polyethylene glycol derivatives of mono- or di-glycerides; mono- and polyglycerol derivatives, such as polyglycerol polyricinoleate; sorbitan esters; polysorbates and polyethylene oxide. Mixtures of any of the above nonionic surfactants may be used.
[0094] As described above, the method of treating the surface of a filled microporous membrane further comprises (2) subjecting the membrane of (1) to conditions sufficient to effect a condensation reaction between the inorganic filler and the silane-functional polyamine compound.
[0095] In the "wet method", the treatment composition can be applied to one or more surfaces of the microporous membrane and rinsed with water to achieve a condensation reaction between the inorganic filler and the (a) acrylic polymer. The wet method can be effectively used to treat the microporous membrane when the microporous membrane is in sheet form, or when the microporous membrane is a component of an existing or prefabricated separation device, such as a hollow fiber, a tubular device, a filtration membrane component of a spiral wound or pleated filtration device, or as a separation membrane of a battery component (e.g., a battery separator). The sheet can be pre-wetted or dried before treatment with the treatment composition.
[0096] In the "dry method" in which the condensation reaction is achieved in step (2) of the disclosed method, the condensation reaction between the inorganic filler and (a) acrylic polymer is achieved by drying the film. When the vapor pressure of the base (b) is ≥1Pa, the dry method can be used. The dry method is particularly useful for the treatment of microporous membranes in sheet form. The dry method can be started on the microporous membrane before any stretching, or after the machine direction stretching and before the transverse stretching, or the dry method can be started on the microporous membrane that has undergone biaxial stretching. Similarly, when the dry method is adopted, in addition to the stretching before the treatment composition is treated or instead of the stretching before the treatment composition is treated, the microporous membrane can be stretched during the drying / heating step. In the process of applying the treatment composition by the dry method, it should be noted that the microporous membrane to which the corresponding treatment composition is applied should remain dimensionally stable during the application and drying steps. In addition, during the dry method drying / heating step, the membrane is usually kept under tension to prevent / minimize shrinkage, regardless of whether the stretching occurs simultaneously.
[0097] The drying temperature to effect the condensation reaction may occur in a temperature range of at least 20° C. and up to 145° C., or up to 120° C., or up to 100° C., or up to 95° C. Exemplary temperature ranges include 20° C.-145° C., 20° C.-120° C., 20° C.-100° C., and 20° C.-95° C.
[0098] In certain embodiments of the method, the membrane produced by step (2) at this point can be formed into a filtration device, such as a hollow fiber, a tubular device, a spiral wound filter device, or a pleated filter device, which can be in the form of a filter cartridge, depending on the intended application. Alternatively, the membrane can be formed into a filtration device after any subsequent processing steps.
[0099] The method further includes (3) contacting at least one surface of the silane-treated membrane with a dispersion comprising an amine-functional polysaccharide dispersed in an aqueous medium containing an organic acid to form a polysaccharide-treated membrane. Typically, the silane-treated membrane is immersed in the dispersion, and / or the dispersion can be passed through the membrane (once) or circulated (multiple times) through the membrane at ambient temperature for about 15 to 30 minutes. "Ambient temperature" refers to the surrounding temperature without the application of heat or other energy. Ambient temperature is typically in the range of 60 to 90°F (15.6 to 32.2°C), such as typical room temperature, 72°F (22.2°C).
[0100] Examples of amine-functional polysaccharides include polygalactosamine, polymannosamines, polyfructosamines, polyglucosamines, etc. Common polyglucosamines include poly-D-glucosamine and chitosan, which is a partially deacetylated poly-N-acetyl-D-glucosamine derived from the shells of crustaceans (note that a deacetylation degree of greater than 60% is most suitable). To the extent that the polysaccharide is soluble in an acidic solution, the amine-functional polysaccharide may be present in the dispersion in an amount of at least 0.25 wt%, or at least 0.50 wt%, or at least 0.75 wt%, and at most 15 wt%, or at most 10 wt%, or at most 5 wt%, based on the total weight of the dispersion.
[0101] Examples of organic acids that can be used in the aqueous medium include formic acid, acetic acid, lactic acid, benzoic acid, propionic acid, etc. A mixture of acids can also be used. The pH of the dispersion is adjusted to a pH below 6.5, for example 1-6, with an organic acid.
[0102] At least one surface of the polysaccharide-treated membrane formed in (3) is then contacted with (4) an aqueous solution of an acid which at least partially neutralizes the amine functional groups on the polysaccharide (thereby forming ammonium salt groups), and then (5) contacted with an amine-functional alkoxysilane to form a polysaccharide hydrogel layer on the membrane. Likewise, in each of these steps, the membrane may be immersed in the relevant treatment solution and / or the relevant treatment solution may be passed through the membrane or circulated through the membrane at ambient temperature.
[0103] The aqueous solution of the acid used in step (4) can be an organic acid or an inorganic acid; typically, the aqueous solution of the acid includes an inorganic acid such as boric acid, sulfuric acid or phosphoric acid. A mixture of acids can also be used. The acid can have 2 or more protons, which can form ammonium salts on the amine groups present on the polysaccharide and form a loosely cross-linked network (not being bound by theory).
[0104] The amine-functional alkoxysilane may include aminopropyltriethoxysilane, aminopropyltrimethoxysilane, aminobutyltriethoxysilane, aminobutyltrimethoxysilane, aminophenyltrimethoxysilane, 3-aminopropyltri(methoxyethoxyethoxy)silane, 11-aminoundecyltriethoxysilane, 2-(4-pyridylethyl)triethoxysilane, aminopropylsilanetriol, 3-(m-aminophenoxy)propyltrimethoxysilane, 3-aminopropylmethyldiethoxysilane, 3-aminopropylmethyldiethoxysilane, 3-aminopropyldimethylethoxysilane, or some combination thereof. The amine-functional alkoxysilane may include polyaminosilane. Non-limiting examples of polyaminosilanes include: N-(2-aminoethyl)-3-aminopropyltriethoxysilane, N-(2-aminoethyl)-3-aminopropyl-silanetriol, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, N-(2-aminoethyl)-3-aminoisobutylmethyldimethoxysilane, bis(2-hydroxyethyl)-3-aminopropyltriethoxysilane, diethylaminomethyltriethoxysilane, N,N-diethyl-3-aminopropyl)trimethoxysilane, 3-(N-phenylvinylmethyl-2-aminoethylamino)propyltrimethoxysilane hydrochloride, N-trimethoxysilylpropyl-N,N,N-trimethylammonium chloride, N-(trimethoxysilylethyl)benzyl-N,N,N-trimethylammonium chloride, trimethoxysilylpropyl modified (polyethyleneimine) or some combination thereof.
[0105] Alternatively, the amine-functional alkoxysilane may comprise the reaction product of (i) a polyamine having at least one primary amino group and / or at least one secondary amino group and (ii) an epoxy-functional silane. In this example, the polyamine (i) used to form the amine-functional alkoxysilane may include polyethyleneimine, N-(3-aminopropyl)-1,4-butanediamine, N,N'-bis(3-aminopropyl)-1,4-butanediamine, N-(3-aminopropyl)-N'-[3-[(3-aminopropyl)amino]propyl]propane-1,3-diamine, 1,13-diamino-5,9-diazatridecane, triethylenetetramine, diethylenetriamine, and / or 1-(2-aminoethyl)piperazine. Suitable epoxy-functional silanes for use as epoxy-functional silanes (ii) may be any of those selected from the group consisting of diepoxy-functional silanes, epoxycyclohexylsilanes, epoxycyclohexylalkylsilanes, glycidyloxyalkylsilanes and mixtures thereof. Specific examples of epoxy-functional silanes (ii) for forming amine-functional alkoxysilanes include (3-glycidyloxypropyl)trialkoxysilanes, (3-glycidyloxypropyl)bis(trimethylsiloxy)methylsilane, (3-glycidyloxypropyl)dimethylethoxysilane and / or (3-glycidyloxypropyl)methyldiethoxysilane.
[0106] The reaction of the polyamine with the epoxy-functional silane containing at least one condensable or hydrolyzable group can be carried out "neat" or in the presence of a solvent. The reaction of the polyamine with the epoxy-functional silane can be carried out in a polar solvent. Some non-limiting examples of suitable polar solvents that can be used include those disclosed above; in particular, water or an alcohol, such as C 1 To C 6 Alcohol, or water and C 1 To C 6 A mixture of one or more of alcohols. Suitable C 1 To C 6 Alcohol can be any kind of those in the group consisting of free methanol, ethanol, 1-propanol, isopropanol, 1-butanol, 2-butanol, 1-hexanol and mixtures thereof. Acids such as acetic acid, hydrochloric acid, sulfuric acid, nitric acid, carbonic acid, lactic acid, citric acid, phosphoric acid and / or oxalic acid can be present to help dissolve the polyamines. Acids can be present in the reaction mixture in an amount greater than 0 wt %, or at least 1%, and up to 10%, or up to 5% or up to 2% by weight, based on the gross weight of the reaction mixture. For example, acids can be present in the reaction mixture in an amount greater than 0 to up to 10%, or greater than 0 to up to 5%, or greater than 0 to up to 2%, or 1 to 10%, or 1 to 5%, or 1 to 2%. The solution can be used as a treatment composition containing silane-functional polyamines, or a portion of the solvent can be removed, for example, by stripping or distillation techniques known in the art. In addition, the reaction of polyamines with epoxy-functional silanes can be achieved by heating. The exact reaction temperature depends on a variety of factors, including the type of the specific reactant selected and the solvent used. However, the temperature will typically range from ambient temperature to 90°C and the reaction time may be several hours, for example up to 5 hours, such as 0.5 hour to 2 hours.
[0107] Typically, the molar ratio of the sum of primary and secondary amino groups present in the polyamine (i) to the epoxy groups present in the epoxy-functional silane (ii) is 1:1 to 100:1, such as 3:1 to 50:1, or 4:1 to 40:1, or 6:1 to 25:1.
[0108] Amine functional alkoxysilanes typically include 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, 3-trimethoxysilylpropyl)diethylenetriamine, trimethoxysilylpropyl modified (polyethyleneimine) and / or dimethoxysilylmethylpropyl modified (polyethyleneimine).
[0109] The amine functional alkoxysilane may be combined with a surfactant, particularly a nonionic surfactant. Suitable examples include those described previously.
[0110] It is believed that steps (4) and (5) allow the formation of a polysaccharide hydrogel layer on the membrane. As used herein, "hydrogel" is a water-insoluble 3-dimensional network of physically or chemically bound polymer chains that can trap water in the spaces between molecules. Typically, the treated microporous membrane is kept moist after treatment and during storage, for example by filling with an aqueous solution, to prevent degradation of the hydrogel on the membrane surface.
[0111] The present invention further relates to a method of treating a filtration device comprising a microporous membrane comprising: an organic thermoplastic substrate; a finely divided particulate, substantially water-insoluble inorganic filler distributed throughout the substrate; a network of interconnected pores communicating throughout the microporous membrane, and an acid-functional acrylic layer on at least one surface of the microporous membrane, wherein the acid-functional acrylic layer is bonded to the filler via siloxane functional groups. An example of a suitable filtration device can be formed from a microporous membrane treated according to steps (1) and (2) of the above method. A typical filtration device is in the form of a hollow fiber, tubular device, spiral wound filter device, or pleated filter device, typically contained within a filter cartridge.
[0112] In the method for treating a filtration device of the present disclosure, (1) at least one surface of an acid-functional acrylic layer on a microporous membrane is contacted with a dispersion comprising an amine-functional polysaccharide dispersed in an aqueous medium containing organic matter to form a polysaccharide-treated membrane. Such a dispersion may include any of those disclosed above.
[0113] At least one surface of the polysaccharide-treated film formed in (1) is then contacted (2) with an aqueous solution of an acid, followed by (3) contacting with an amine-functional alkoxysilane to form a polysaccharide hydrogel layer on the film. The aqueous solution of the acid used in step (2) can be an organic acid or an inorganic acid; typically, the aqueous solution of the acid includes the above inorganic acids. Similarly, the amine-functional alkoxysilane used in step (3) typically includes 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, 3-trimethoxysilylpropyl)diethylenetriamine, trimethoxysilylpropyl-modified (polyethyleneimine) and / or dimethoxysilylmethylpropyl-modified (polyethyleneimine).
[0114] Alternatively, the amine-functional alkoxysilane may comprise the reaction product of (i) a polyamine having at least one primary amino group and / or at least one secondary amino group and (ii) an epoxy-functional silane. Examples of the polyamine (i) and epoxy-functional silane (ii) used to form the amine-functional alkoxysilane include any of those disclosed above.
[0115] Each of the steps (1) to (3) of the method for treating a filtration device can be carried out in a manner similar to the similar process steps in the above-mentioned method for treating the surface of a microporous membrane. Likewise, the membrane on the treated filtration device is usually kept wet after treatment and during storage to prevent degradation of the hydrogel on the membrane surface.
[0116] The present invention further relates to a treated microporous membrane comprising: (1) a microporous membrane comprising an organic thermoplastic substrate; a finely divided particulate, substantially water-insoluble inorganic filler distributed throughout the substrate; and a network of interconnected pores communicating throughout the microporous membrane; (2) an acrylic layer on at least one surface of the microporous membrane, wherein the acrylic layer is bonded to the filler via siloxane functional groups; (3) a hydrogel layer on at least one surface of the acrylic layer, wherein the hydrogel layer is formed from an amine-functional polysaccharide and an amine-functional alkoxysilane. The treated microporous membrane can be in the form of a sheet, and / or a component of a filtration device, such as a hollow fiber, a tubular device, a spiral wound filter device, or a pleated filter device, and / or in a filter cartridge, depending on the intended application. The treated microporous membrane can be prepared, for example, using the methods described above.
[0117] The microporous membrane (1) generally comprises any of those mentioned above. For example, the organic thermoplastic substrate may comprise polyacrylonitrile, cellulose nitrate, polycarbonate, cellulose acetate, polytetrafluoroethylene (PTFE), polyamide, polyolefin, polyetherketone, polyvinylidene fluoride (PVDF), polysulfone and / or polyethersulfone, and the filler may comprise silicon dioxide, aluminum oxide, calcium oxide, zinc oxide, magnesium oxide, titanium oxide and / or zirconium oxide. The microporous membrane (1) generally comprises a polyolefin substrate and a silicon dioxide filler.
[0118] The acrylic layer (2) may be formed from a mixture of vinyl monomers comprising: (i) a (meth) acrylic monomer and (ii) a silane-functional acrylic monomer. Monomers (i) and (ii) may be any of those disclosed above. In a specific example, the mixture of vinyl monomers used to form the acrylic layer (2) further comprises (iii) N-vinyl pyrrolidone.
[0119] As described above, the treated microporous membrane further comprises a hydrogel layer (3) located on at least one surface of the acrylic layer. The hydrogel layer is formed from the amine-functional polysaccharide and amine-functional alkoxysilane as described above (the amine groups may be converted into ammonium salt groups in advance). The hydrogel layer may be formed using any of the amine-functional polysaccharides and amine-functional alkoxysilanes disclosed above.
[0120] It has been found that the treated membranes of the present disclosure and the treated membranes and filtration devices prepared by the disclosed methods exhibit longer practical life when used in oil-water separation applications, as evidenced by reduced fouling, increased flow rates, and durability to cleaning procedures over extended periods of time compared to equivalent untreated membranes. Such membranes may also exhibit increased oil retention, particularly at high operating pressures; i.e., pressures above 15 psi, such as above 30 psi, or above 40 psi, and pressures up to 100 psi.
[0121] The following working examples are intended to further describe and demonstrate the films and treatment methods described herein. It should be understood that the disclosure described in this specification is not necessarily limited to the examples described in this section. Components mentioned elsewhere in the specification as alternative materials suitable for use but not shown in the working examples below are expected to provide results comparable to their displayed counterparts. Unless otherwise stated, all parts are by weight.
[0122] Examples
[0123] Part 1: Membrane production and processing methods
[0124] An extruded sheet was prepared according to Example M-2 of US 10,888,821 A1 and used as the substrate for all the following examples.
[0125] Part 1. Preparation of treatment compositions
[0126] Part 1a. Preparation of acrylic polymer dispersion :
[0127] The acrylic polymer was prepared from the following components listed in Table 1.
[0128] Charge A was placed in a 4-neck round bottom flask with a condenser, nitrogen adapter, mechanical stirrer and addition funnel, and the reaction was heated to 80°C with stirring under a nitrogen blanket. Charges B and C were then added simultaneously over three hours at reflux, and then maintained at reflux for another two hours. Charge D was then added over thirty minutes at 80°C. The reaction mixture was maintained at 80°C for another two hours. The clear solution was then cooled to 50°C and poured into Charge E over fifteen minutes with stirring. The solution was stirred for 30 minutes, and then filtered through a 100 micron mesh filter bag. The solids percentage was checked by heating the sample at 110°C in an oven for 1 hour (10.36% solids)
[0129] Table 1. Acrylic polymer composition
[0130]
[0131] Part 1b. Acrylic acid treatment liquid
[0132] To a polyethylene beaker equipped with an air-driven paddle stirrer was added water and 2-butoxyethanol according to the amounts in Table 2. After stirring for 5 minutes, the acrylic polymer dispersion from Part 1a was slowly added to give a solution with a pH between 9 and 10.
[0133] Table 2. Acrylic acid treatment solution
[0134]
[0135] Part 1c. Preparation of polysaccharide treatment solution :
[0136] A 1 wt% solution of chitosan (from shrimp shells, > 75% deacetylated) in 2% acetic acid was prepared by stirring until the solids were completely dissolved.
[0137] Part 1d. Preparation of amine-functional alkoxysilane treatment fluids
[0138] Charge cold water to a polyethylene beaker equipped with an air-driven paddle stirrer and stir to create a vortex of approximately 1". Add the specified amount of poly(2-ethyl-2-oxazoline) and stir for 4 hours. Add 2-butoxyethanol and surfactant and stir the solution for an additional 30 minutes. Then add 3-aminopropyltriethoxysilane and stir the solution for 15 minutes. Add the trimethoxysilylpropyl-polyethyleneimine solution to the main mixing container and stir for at least 5 minutes before use.
[0139] Table 3. Preparation of the second treatment solution
[0140]
[0141] 1 Average molecular weight 50,000, provided by Sigma Aldrich.
[0142] 2 Block copolymer surfactants, reported weight average M w The product is 2150 and can be obtained from BASF.
[0143] 3 A 50% solution in isopropyl alcohol sold by Gelest Corporation under product code SSP-060.
[0144] 4 Branched polyethyleneimine, reported average Mn of 10,000 and Mw of 25,000, was purchased from Sigma-Aldrich, product number 408727.
[0145] Part 2. Membrane treatment
[0146] Example 1
[0147] Step 1.
[0148] A piece of microporous membrane was cut to approximately 10.5" x 10.5" and clamped to the periphery of a 12" x 12" metal frame with 1" binder clips. The solution of Part 1b was applied sufficiently to obtain 281 g / m 2 The framed samples were placed in an oven set at 95°C for 10 minutes. The assembly was then allowed to cool to room temperature.
[0149] Step 2.
[0150] The chitosan solution of Part 1c was applied until no more liquid was absorbed into the membrane, as evidenced by pooling of liquid on the surface, which was then wiped off and then kept in a sealed plastic bag for 15 minutes. The treated membrane remained wet in the bag until the next step.
[0151] Step 3.
[0152] Place the membrane from step 2 in 2.5% HO. 2 SO 4 The membrane was then placed in a sealed plastic bag and kept wet until the next step.
[0153] Step 4.
[0154] Completely immerse the membrane from step 3 in the amine-functional silane solution prepared in part 1d. Keep the membrane submerged for 15 minutes and then rinse with water. The membrane is then placed in a sealed plastic bag and kept wet in the bag for testing.
[0155] Comparative Example CE-2:
[0156] A piece of microporous membrane was prepared and followed by step 1 of Example 1 to provide a silane (acrylic) treated membrane.
[0157] Comparative Example CE-3
[0158] One piece of the microporous membrane was untreated and used as Comparative Example CE-3.
[0159] Part 3: Membrane performance tests
[0160] Water flux :Using membrane area is 90cm 2 The Sterlitech filter holder is used to test water flux. The Sterlitech unit with the membrane is filled with 1 liter of water and sealed. The air pressure is set to 50 psi and the time required for 1 liter of water to pass through the membrane is recorded. The corresponding water flux is calculated.
[0161] Oil resistance:Remove the water-wetted membrane of interest from the water flux test apparatus described above and immediately evaluate oil resistance. Use a disposable dropper to place three drops of oil on the membrane surface. Allow all three drops to remain undisturbed for approximately one minute and then wipe off with a paper towel. If the oil drop penetrates and contaminates the membrane, a result rating of 1 is given. If the oil drop remains mostly on the surface but visibly contaminates the membrane, a result rating of 2 is given. If the oil drop remains on the surface, does not penetrate the membrane and / or only slightly contaminates the surface, a result rating of 3 is given.
[0162] Oil absorption test: The membrane samples of 2 cm x 2 cm were immersed in 100% crude oil for 24 hours. The samples were then removed from the oil bath and all excess oil on the surface was wiped off. The resulting samples were placed in a beaker containing 100 ml of hexane, immersed for 5 minutes, and then removed. The corresponding oil concentration in the hexane immersion solution was determined using a TD-3100 from Turner Design Hydrocarbon Instruments.
[0163] Water / Oil Squeeze Pressure Test : 200 ml of water and 50 / 50 volume mixture of Texas crude oil (purchased from Texas Crude) and a membrane area of 90 cm 2 The Sterlitech filter holder is used for testing. Once the Sterlitech unit is fully installed and charged, the test begins with a pressure of 5 psi, and then the pressure is increased in increments of 0.5 psi every 5 minutes. The pressures of water and oil are recorded as they pass through the membrane. The difference between these two pressures is recorded in Table 5 as ΔP Oil-Water. A larger ΔP corresponds to a larger operable pressure window where there is less chance of oil permeating through as a contaminant.
[0164] Table 7. Membrane properties of different membranes A higher ΔP is better suited for higher pressure applications.
[0165] While specific examples of the present invention have been described above for purposes of illustration, it will be apparent to those skilled in the art that various changes may be made in the details of the invention without departing from the invention as defined in the appended claims.
Claims
1. A method for treating the surface of a microporous membrane, the microporous membrane comprising an organic thermoplastic substrate; a finely divided, particulate, substantially water-insoluble inorganic filler distributed throughout said substrate; and a network of interconnected pores communicating throughout the microporous membrane, the method comprising, in sequence: (1) contacting at least one surface of the microporous membrane with a treatment composition to form a silane-treated membrane, the treatment composition comprising: (a) an acrylic polymer prepared from a mixture of vinyl monomers, the mixture comprising: (i) a (meth) acrylic monomer and (ii) a silane-functional acrylic monomer; and (b) optionally, a base, wherein the acrylic polymer is in contact with the filler present in the substrate; (2) subjecting the silane-treated film formed in (1) to conditions sufficient to effect a condensation reaction between the filler and the acrylic polymer; (3) contacting at least one surface of the silane-treated membrane with a dispersion comprising an amine-functional polysaccharide dispersed in an aqueous medium containing an organic acid to form a polysaccharide-treated membrane; (4) contacting at least one surface of the polysaccharide-treated membrane formed in (3) with an aqueous acid solution; and (5) contacting the polysaccharide-treated membrane with an amine-functional alkoxysilane to form a polysaccharide hydrogel layer on the membrane.
2. The method of claim 1, wherein the organic thermoplastic substrate comprises polyacrylonitrile, cellulose nitrate, polycarbonate, cellulose acetate, polytetrafluoroethylene (PTFE), polyamide, polyolefin, polyetherketone, polyvinylidene fluoride (PVDF), polysulfone and / or polyethersulfone.
3. The method according to any one of the preceding claims, further comprising the step of assembling the membrane of step (2) into a hollow fiber, a tubular device, a spiral wound filter device or a pleated filter device before step (3).
4. The method according to any one of the preceding claims, wherein the mixture of vinyl monomers further comprises (iii) N-vinyl pyrrolidone.
5. The method of any one of the preceding claims, wherein the treatment composition of step (1) further comprises (c) at least one of poly(N-vinylpyrrolidone) or polyoxazoline.
6. A method according to any one of the preceding claims, wherein the base comprises an amine.
7. The method of claim 6, wherein the amine comprises a tertiary amine.
8. A method according to any one of the preceding claims, wherein the acrylic polymer has a weight average molecular weight (MW) of up to 35,000 Da, or up to 30,000 Da, or up to 25,000 Da, or up to 20,000 Da, or up to 16,000 Da, or up to 15,000 Da. w ).
9. The method according to any one of the preceding claims, wherein the filler is selected from the group consisting of silica, alumina, calcium oxide, zinc oxide, magnesium oxide, titanium oxide, zirconium oxide and mixtures thereof.
10. The method of any one of the preceding claims, wherein the filler comprises silica.
11. The method of any one of the preceding claims, wherein the silane-treated film formed in (1) is subjected to conditions sufficient to effect a condensation reaction between the filler and the acrylic polymer, comprising drying the film in step (2).
12. The method of claim 11, wherein the drying occurs at a temperature range of 20°C to 145°C, or 20°C to 120°C, or 20°C to 100°C, or 20°C to 95°C.
13. The method of any one of claims 1 to 10, wherein the silane-treated film formed in (1) is subjected to conditions sufficient to effect a condensation reaction between the filler and the acrylic polymer, including adjusting the pH to a range of 4 to 7 in step (2).
14. The method of any one of the preceding claims, wherein the base is included in an amount sufficient to neutralize at least 75% of the acid functional groups on the (meth)acrylic monomers.
15. The method of any one of the preceding claims, wherein the amine-functional polysaccharide comprises polyglucosamine.
16. The method according to any one of the preceding claims, wherein the organic acid used in step (3) comprises formic acid, acetic acid, lactic acid, benzoic acid and / or propionic acid.
17. The method according to any one of the preceding claims, wherein the aqueous acid solution used in step (4) comprises sulfuric acid, phosphoric acid and / or boric acid.
18. The method of any one of the preceding claims, wherein the amine-functional alkoxysilane comprises 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, 3-trimethoxysilylpropyldiethylenetriamine, trimethoxysilylpropyl-modified (polyethyleneimine) and / or dimethoxysilylmethylpropyl-modified (polyethyleneimine).
19. The method of any one of claims 1 to 17, wherein the amine-functional alkoxysilane comprises the reaction product of (i) a polyamine having at least one primary amino group and / or at least one secondary amino group and (ii) an epoxy-functional silane.
20. The method of claim 19, wherein the polyamine (i) comprises polyethyleneimine, N-(3-aminopropyl)-1,4-butanediamine, N,N'-bis(3-aminopropyl)-1,4-butanediamine, N-(3-aminopropyl)-N'-[3-[(3-aminopropyl)amino]propyl]propane-1,3-diamine, 1,13-diamino-5,9-diazatridecane, triethylenetetramine, diethylenetriamine and / or 1-(2-aminoethyl)piperazine.
21. The method of claim 19 or 20, wherein the epoxy-functional silane (ii) comprises (3-glycidoxypropyl)trialkoxysilane, (3-glycidoxypropyl)bis(trimethylsiloxy)methylsilane, (3-glycidoxypropyl)dimethylethoxysilane and / or (3-glycidoxypropyl)methyldiethoxysilane.
22. A treated microporous membrane prepared by a method according to any one of the preceding claims.
23. The treated microporous membrane of claim 22, wherein the membrane contacted with the treatment composition is in the form of a sheet.
24. A method of treating a filtration device comprising a microporous membrane, the microporous membrane comprising an organic thermoplastic substrate; a finely divided particulate, substantially water-insoluble inorganic filler distributed throughout the substrate; a network of interconnected pores communicating throughout the microporous membrane, and an acid-functional acrylic layer on at least one surface of the microporous membrane, wherein the acid-functional acrylic layer is bonded to the filler via siloxane functional groups; the method comprising: (1) contacting at least one surface of the acid-functional acrylic layer on the microporous membrane with a dispersion comprising an amine-functional polysaccharide dispersed in an aqueous medium containing an organic acid to form a polysaccharide-treated membrane; (2) contacting at least one surface of the polysaccharide-treated film formed in (1) with an aqueous acid solution; as well as (3) contacting the polysaccharide-treated membrane with an amine-functional alkoxysilane to form a polysaccharide hydrogel layer on the membrane.
25. The method of claim 24, wherein the organic thermoplastic substrate comprises a polyolefin, a polyetherketone, polyvinylidene fluoride (PVDF), a polysulfone and / or a polyethersulfone.
26. A method according to claim 24 or 25, wherein the filter device is in the form of a hollow fiber, a tubular device, a spiral wound filter device or a pleated filter device.
27. The method according to any one of claims 24 to 26, wherein the filler is selected from the group consisting of silica, alumina, calcium oxide, zinc oxide, magnesium oxide, titanium oxide, zirconium oxide and mixtures thereof.
28. The method of any one of claims 24 to 27, wherein the filler comprises silica.
29. The method of any one of claims 24 to 28, wherein the amine-functional polysaccharide comprises polyglucosamine.
30. The method according to any one of claims 24 to 29, wherein the organic acid used in step (1) comprises formic acid, acetic acid, lactic acid, benzoic acid and / or propionic acid.
31. The method according to any one of claims 24 to 30, wherein the aqueous acid solution used in step (2) comprises sulfuric acid, phosphoric acid and / or boric acid.
32. The method of any one of claims 24 to 31, wherein the amine-functional alkoxysilane comprises 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, 3-trimethoxysilylpropyl)diethylenetriamine, trimethoxysilylpropyl-modified (polyethyleneimine) and / or dimethoxysilylmethylpropyl-modified (polyethyleneimine).
33. The method of any one of claims 24 to 31, wherein the amine-functional alkoxysilane comprises the reaction product of (i) a polyamine having at least one primary amino group and / or at least one secondary amino group and (ii) an epoxy-functional silane.
34. The method of claim 33, wherein the polyamine (i) comprises polyethyleneimine, N-(3-aminopropyl)-1,4-butanediamine, N,N'-bis(3-aminopropyl)-1,4-butanediamine, N-(3-aminopropyl)-N'-[3-[(3-aminopropyl)amino]propyl]propane-1,3-diamine, 1,13-diamino-5,9-diazatridecane, triethylenetetramine, diethylenetriamine and / or 1-(2-aminoethyl)piperazine.
35. The method of claim 33 or 34, wherein the epoxy-functional silane (ii) comprises (3-glycidoxypropyl)trialkoxysilane, (3-glycidoxypropyl)bis(trimethylsiloxy)methylsilane, (3-glycidoxypropyl)dimethylethoxysilane and / or (3-glycidoxypropyl)methyldiethoxysilane.
36. A treated filtration device prepared by the method of any one of claims 24 to 35.
37. A treated microporous membrane comprising: (1) A microporous membrane comprising an organic thermoplastic substrate; a finely divided, particulate, substantially water-insoluble inorganic filler distributed throughout the substrate; and a network of interconnected pores extending throughout the microporous membrane; (2) an acrylic layer on at least one surface of the microporous membrane, wherein the acrylic layer is bonded to the filler through siloxane functional groups; and (3) A hydrogel layer on at least one surface of the acrylic layer, wherein the hydrogel layer is formed of an amine-functional polysaccharide and an amine-functional alkoxysilane.
38. The treated microporous membrane of claim 37, wherein the organic thermoplastic substrate comprises a polyolefin, a polyetherketone, polyvinylidene fluoride (PVDF), a polysulfone, and / or a polyethersulfone.
39. The treated microporous membrane of any one of claims 37 to 38, wherein the filler is selected from the group consisting of silica, alumina, calcium oxide, zinc oxide, magnesium oxide, titanium oxide, zirconium oxide, and mixtures thereof.
40. The treated microporous membrane of any one of claims 37 to 39, wherein the acrylic layer is formed from a mixture of vinyl monomers comprising: (i) a (meth)acrylic monomer and (ii) a silane-functional acrylic monomer.
41. The treated microporous membrane of claim 40, wherein the mixture of vinyl monomers further comprises (iii) N-vinyl pyrrolidone.
42. The treated microporous membrane of any one of claims 37 to 41, wherein the amine-functional polysaccharide comprises polyglucosamine.
43. The treated microporous membrane of any one of claims 37 to 42, wherein the amine-functional alkoxysilane comprises 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, 3-trimethoxysilylpropyl)diethylenetriamine, trimethoxysilylpropyl-modified (polyethyleneimine) and / or dimethoxysilylmethylpropyl-modified (polyethyleneimine).
44. The treated microporous membrane of any one of claims 37 to 42, wherein the amine-functional alkoxysilane comprises the reaction product of (i) a polyamine having at least one primary amino group and / or at least one secondary amino group and (ii) an epoxy-functional silane.
45. The treated microporous membrane of claim 44, wherein the polyamine (i) comprises polyethyleneimine, N-(3-aminopropyl)-1,4-butanediamine, N,N'-bis(3-aminopropyl)-1,4-butanediamine, N-(3-aminopropyl)-N'-[3-[(3-aminopropyl)amino]propyl]propane-1,3-diamine, 1,13-diamino-5,9-diazatridecane, triethylenetetramine, diethylenetriamine and / or 1-(2-aminoethyl)piperazine.
46. The treated microporous membrane of claim 44, wherein the epoxy-functional silane (ii) comprises (3-glycidoxypropyl)trialkoxysilane, (3-glycidoxypropyl)bis(trimethylsiloxy)methylsilane, (3-glycidoxypropyl)dimethylethoxysilane and / or (3-glycidoxypropyl)methyldiethoxysilane.
47. The treated microporous membrane of any one of claims 37 to 46, wherein the membrane is a component of a hollow fiber filtration device, a tubular filtration device, a spiral wound filtration device, or a pleated filtration device.
Citation Information
Patent Citations
Method for treating a microporous membrane
US10888821B2
Coated microporous materials having filtration and adsorption properties and their use in fluid purification processes
US20140069862A1
Method of preparing silica pigments
US2940830A
Preparation of amorphous, precipitated silica and siliceous filler-reinforced microporous polymeric separator
US4681750A
Microporous material
US5196262A